Caracterización del fitoplancton del perfil costero del cantón Machala en las zonas Chivería Huaylá Puerto Bolívar El Coco Puerto Grande - Sanmartín Espinoza, Luis Fernando (2012)
The present research focused on determining the characterization of phytoplankton in the coastal profile of Canton Machala. The study was conducted in areas of Chivería, Huaylá, Puerto Bolivar, El Coco, Puerto Grande, where it was determined qualitatively phytoplankton concentration in each of the areas, in laboratories Planctonologia of the Faculty of Agricultural Sciences. This investigation lasted four months, which aimed to: Characterize the phytoplankton species present in the coastal marine profile Machala Canton phytoplankton was determined that: the class Bacillariophyceae (diatoms) had the greatest percentage in Puerto Grande site with 76.65%, followed by 75.38% Chivería estuary, the estuary Santa Rosa with a 66.53%, Coconut site with 55.30% and 52.76% with Huaylá estuary. For dinoflagellates, are presented with the highest percentage in the Coco site with 27.94%, followed by Santa Rosa creek with 23.43%, the Estero Chivería with 22.94%, and 16.87 Huaylá with site 9.15% Puerto Grande. With Cyanophyceae class (Cyanophyta) the highest percentage was found in the estuary Huaylá with 30.37%, followed by the large port site with 7.10%, the site with 6.84% Coco and Santa Rosa creek with 2 , 51%, not the species of algae found in the estuary Chivería. In class Chlorophyceae (Chlorophyta) with highest percentage meeting on site with 9.92% coconut, Estero Santa Rosa with 7.53%, Puerto large site with 7.1% and 1.68% with Chivería estuary. In general representation and percentage of test results, identified sites for phytoplankton, prove that the Bacillariophyceae (diatoms) dominate with 65.99%, on the Dinophyceae (dinoflagellates) 20.46%, Cyanophyceae (cyanobacteria) 7 , 42% and Chlorophyceae (Chlorophyta) 6.13%.